(untitled) (REVISTA CIENTÍFICA SIGNOS FÓNICOS, 2022)
INTRODUCTION: This research aims to communicate the level of emotional intelligence in university students of the psychology program at the University of Santander, for this, the importance of three main dimensions has been taken into account which are the recognition, expression and control of emotions, because the educational environment is a variable that affects the quality of the training of professionals, as well as the assimilation of knowledge. The main objective is to determine the degree of recognition, expression and control of emotions that determines the influence on the educational environment of psychology students at the University of Santander. METHOD: Quantitative and descriptive approach, which allowed to analyze the results of the scale applied to 113 students. RESULTS: The final structure of the scale, according to the factor analysis, was established under 3 dimensions: Recognition of Emotions (9 items); Expression of Emotions (8 items), and Control of emotions (8 elements).